2022
DOI: 10.3389/fmicb.2022.917051
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of Gut Microbiota and Lipidomics of Content Induced by Dietary Methionine Restriction in Rice Field Eel (Monopterus albus)

Abstract: An 8-week feeding trial was conducted using the rice field eel (Monopterus albus) with six isonitrogenous and isoenergetic experimental diets of basic feed supplemented with different levels of methionine (0, 2, 4, 6, 8, or 10 g/kg). This study built upon previous research findings that showed dietary methionine restriction (M0, 0 g/kg) inhibited hepatic fatty acid metabolism and intestinal fatty acid transportation, but both are improved by dietary supplementation with a suitable level of methionine (M8, 8 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The metabolism of methionine through the transmethylation pathway generates S-adenosylmethionine, which is important for the methylation of lipids, and proteins ( Dash et al, 2016 ). Hu et al (2022) found that methionine restriction altered the microbial community balance and functions, while methionine supplementation enhanced the stability of gut microbiota and lipid metabolism of fish. According to Lee et al (2021) , heat-stressed chicks fed with L-Methionine had reduced intestinal blood vessel formation and maintained normal glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The metabolism of methionine through the transmethylation pathway generates S-adenosylmethionine, which is important for the methylation of lipids, and proteins ( Dash et al, 2016 ). Hu et al (2022) found that methionine restriction altered the microbial community balance and functions, while methionine supplementation enhanced the stability of gut microbiota and lipid metabolism of fish. According to Lee et al (2021) , heat-stressed chicks fed with L-Methionine had reduced intestinal blood vessel formation and maintained normal glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…Seaweed extract at 2 ml/L inclusion increased the pathway of gluconeogenesis, TCA and peptidoglycan among heat-stressed birds in our study. Metabolic pathways such as gluconeogenesis and TCA have inhibition potential against pathogenic bacteria ( Hu et al, 2022 ). Enhanced biosynthesis of peptidoglycan may increase the abundance of lactic acid bacteria populations in the gut, partially facilitating the growth benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Although broad bean is rich in a wide range of nutrients, the amino acid composition of broad bean is unbalanced, especially lacking in methionine (Meng et al, 2021). Methionine is one of the essential amino acids for aquatic animals, and its deficiency caused intestinal flora disorders and liver fat accumulation (Hu et al, 2022;Yang et al, 2024). We also observed this phenomenon in the livers of grass carp fed a single broad bean diet, suggesting that methionine deficiency in broad bean may be one of the key factors causing liver steatosis in grass carp.…”
Section: Analysis and Treatment Of Potential Factors Inducing Hepatic...mentioning
confidence: 99%
“…The rice-fish system (RFS), a "globally important agricultural heritage system" [1], is an integrated agri-aquaculture system (IAAS) that combines rice cultivation with aquaculture [2,3]. Compared to rice monoculture, a wide range of aquatic species (i.e., fish, carp, crabs, eel, and softshell turtles) are used in the RFS [4,5]. Rice and various animal species raised in the same system influence each other to balance the role of the rice-field ecosystem [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on rice-fish systems have focused on the ecology of aquatic animals [15][16][17], biodiversity conservation [1,5,18], and economic value [3,9]. In addition, an increasing number of studies on the gut microbial community of aquaculture animals raised in the RFS have been conducted using both DGGE technology and 16S rRNA sequencing, such as in the rice field eel (Monopterus albus) [4,19], carp [13,20], loach [21], and yellow catfish [22].…”
Section: Introductionmentioning
confidence: 99%